FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK TIDAK AMAN PEMANDU WISATA TUBING OPERATOR X GOA PINDUL - Santi Wulandari; Siswi Jayanti; Baju Widjasena (Jurnal Kesehatan Masyarakat, 2019)
One of the causes of accidents is an unsafe practice. Unsafe practice can be caused by 3 factors, predisposing factors such as knowledge and attitudes, reinforcing factors such as supervision and enabling factors such as training of occupational safety and health. Tourism is a sector that need to get attention related to work safety, especially tubing tour guides. The purpose of this study is to analyzed the relationship between knowledge, attitudes, supervision and training of occupational safety and health with unsafe practice in Operators X’s tour guides of Goa Pindul. This type of research was observational analytic with cross-sectional research section. The subjects of this study were 37 Operator X’s tubing tour guides of Goa Pindul. Data colletion was carried out by used a questionnaire instrument and observation sheet. Statistical analysis used the chi-square test. The test results showed that there was a correlation between attitude (p value = 0.014) and supervision (p value = 0.005) with unsafe practice of Operator X’s tubing tour guides of Goa Pindul. There was no correlation between knowledge (p value = 0.062) and OSH training (p value = 0.072) with unsafe practice of Operator X’s tubing tour guides of Goa Pindul. Suggestions for management was to added an OSH sosializations at the routine meeting of the guides, gave routine directions every day before the guiding activities. And suggestions for guides was to followed the OSH socializations and training activities carried out by management and ensure to always following work procedures that have been set.